Hazard identification, risk assessment and risk control (HIRARC) for the use of calcium carbide (CAC2) as ripening agent among mango farmers in northern region of Malaysia - Ismail, Noor Shaeda; Rasdi, Irniza (2019)
The objective of this study is to identify hazard, risk and recommended control mechanism for CaC2 handling through HIRARC. The assessment was determined using DOSH risk matrix, DOSH risk ranking and hierarchy of control tools which incuded elimination, substitution, isolation, engineering controls, administrative controls and personal protective equipments (PPE). From this study, there were three activities determined in this study that have a capacity to instigate hazards to farmers which were carbide wrapping, ripening process and fruits checking after ripening process is over. There were for type of controls applied in this process and it’s included engineering control, isolation, administrative and PPE. In conclusion, there is a need to conduct HIRARC because it is considered as preventive measures since control is applied when hazard has been identified and analyzed, and its associated risk are assessed.